Emporiatrics: The Travellers Medicine - R Sushma; D Nagabhushana (Tehran University of Medical Sciences, 2012)
Travel broadens the mind" and people have been extolling the merits of travel for a very long time .The general belief is that travel is good for travelers mentally and physically. But while travel can indeed be interesting and exciting, and good for mental and physical wellbeing, all too often it can be harmful to a traveler's health (1) .The increase in numbers of travellers and the speed at which they travel has not only had economic, cultural, and social repercussions, but medical, epidemiological, and medico-legal consequences as well. Travel medicine or Emporiatrics is the branch of medicine that deals with the prevention and management of health problems of international travelers (2). The art of travel medicine is selecting the necessary prevention strategy without unnecessary adverse events, cost or inconvenience" (3). Travel health advice is primarily aimed at prevention, and is therefore offered before travel. It includes steps taken before travel like Medical examinations and screening, Psychological preparation, Provision of a medical kit, First aid training, Preventive measures for prevention of thermal injury, Insure and plan for aeromedical evacuation and repatriation, Advice regarding accidents and related hazards, Special provisions for specific travel hazards and Protection against tropical diseases. There is also an aspect of travel health which is provided after return from travel, which is usually diagnostic (4,5). Giving adequate advice on travel health requires a good knowledge about local health hazards overseas, public health measures, and the effectiveness of immunization and prophylaxis. In summary, travel medicine will be established as an interdisciplinary special discipline in the next years and will be characterized by new risks and on the other hand by new methods of therapy and prophylaxis.